TPACK Analysis of 7th Grade English Teacher in Merdeka Curriculum at Sukaraja Commissariat - Persada, Intan Dwi; Mutiara, Dewi; Jamil, Ikram (JEdu: Journal of English Education, 2024)
The importance of technology skills for teachers in the educational process, particularly in teaching English, prompted this research. The Merdeka Curriculum enables teachers to incorporate technology into their lessons. The purpose of this study is to find out TPACK competence, TPACK level, and the factors that hinder 7th Grade English teachers in the Merdeka Curriculum at Sukaraja Commissariat, Sukabumi Regency. This research is a qualitative descriptive approach with data drawn from surveys, interviews, and classroom observations. The results indicated that teachers were at different levels of technological sophistication, with the majority being in the "Medium" group for technology use. It was reinforced by the score of each individual teacher. Respondent 1 achieved a total score of 70, which reflects 67% of the target. Respondent 2 obtained a score of 85, with an achievement level of 81%. Respondent 3 obtained a score of 76, corresponding to an achievement of 72%, while respondent 4 obtained a score of 71, with an achievement level of 68%. Educators possessing good TPACK exhibit the capability to choose and utilize suitable technologies to enhance teaching English. There are several factors that hinder teachers. First, internal factors include motivation, ability, and teacher self-support. Second, external factors include school policies, infrastructure support, and technology training.